SAT-LB81 Carbohydrate Crash: A Rare Case of Thyrotoxic Periodic Paralysis - Sittol, Rani (J Endocr Soc, 2020)
IntroductionThyrotoxic Hypokalemic Periodic Paralysis (TPP) is an uncommon diagnosis in the western world and may be the initial presentation of hyperthyroidism. CaseA healthy 37 year old Asian male was visiting the US when he had sudden onset lower limb weakness after carbohydrate rich meal on Saturday night. He reported hand tremors for 1 month and a 10kg weight loss. On examination he was anxious with a fine hand tremor, BP 158/80mmHg, and HR 106bpm. He had grade 2/5 power to lower limb proximal muscles and brisk reflexes. Thyroid and eyes were normal. Laboratory results significant for potassium (K) 3.2mmol/l, TSH 0.005 (0.270-4.4uiu/ml), FT4 2.6 (0.8-2.2ng/dl), FT3 12.4 (2.77-5.27 pg/ml) and TSH Receptor antibody was 23.9% (<16%). Thoracolumbar MRI was normal. Repletion of K resulted in total resolution of paresis. He was given propranolol and methimazole and chose to complete workup in China.Clinical LessonTPP results in paralysis due to hypokalemia and hyperthyroidism and can be the initial presentation of hyperthyroidism. It is most common in Asian males 20-40 years with incidence 1.9%, but only 0.2% in the west. Proximal muscles are affected more. Attacks may be precipitated by carbohydrate load, rest after exercise, or stress. Patients tend to present on weekends between 2100-0900hrs. It is hypothesized that K metabolism is diurnal, with influx to muscle at night or at rest. Once euthyroid, TPP will not recur unlike familial hypokalemic periodic paralysis which is recurrent and of earlier onset. The underlying reason remains unclear. It may be related to the action of thyroxine on Na/K-ATPase pump. TPP is usually associated with Graves’ disease, but other causes of hyperthyroidism have been reported. TPP is a treatable rare illness in Asians, and very uncommon in the West. Physicians must be aware of its subtleties, as it may be confused with other more common conditions.ReferencesChang-Hsun Hsieh, Shi-Wen Kuo, Dee Pei, Yi-Jen Hung, Sandra Chyi-Fan, Ling-I Wu, Chih-Tsueng He, Tsao-Chin Yang, Wei-Cheng Lian, and Chien-Hsing Lee, Thyrotoxic periodic paralysis: an overview, Ann Saudi Med. 2004 Nov-Dec; 24(6): 418-422. doi:10.5144/0256-4947.2004.418Annie W. C. Kung, CLINICAL REVIEW: Thyrotoxic Periodic Paralysis: A Diagnostic Challenge, The Journal of Clinical Endocrinology and Metabolism 91(7):2490-2495, Copyright © 2006 by The Endocrine Society doi: 10.1210/jc.2006-0356